2002
DOI: 10.1002/1521-3765(20020816)8:16<3747::aid-chem3747>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Epothilone A through Stereospecific Epoxidation of the p-Methoxybenzyl Ether of Epothilone C

Abstract: Nano‐peapods: Magnetically responsive photonic nanochains have been produced by inducing chain alignment of uniform magnetic particles during their silica coating process and then allowing additional deposited silica to wrap entire structures. The optical diffraction of these nanochains can be switched on and off by applying magnetic fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…No such effect was observed upon simultaneous treatment with these agents or if Apo-2L/TRAIL treatment preceded treatment with BMS-247550 (20) [106]. It has also been reported that ectopic overexpression of Smac/DIABLO in human acute leukemia Jurkat T-cells or co-treatment with the N-terminal tetra-or heptapetide of this protein significantly enhance the apoptosis-inducing effects of BMS-247550 (20) in this cell line [107]. It is worth noting that Bhalla and coworkers strongly emphasize that their studies in A2780-1A9 cells would indicate that "apoptosis of A2780-1A9 cells follows [BMS-247550 (20)-induced] mitotic arrest, which is not associated with a marked increase in the levels of survivin" (cf., however, the recent work by Horwitz and coworkers [34,35]).…”
Section: Epothilone Analogs In Clinical Develop-mentsupporting
confidence: 52%
See 4 more Smart Citations
“…No such effect was observed upon simultaneous treatment with these agents or if Apo-2L/TRAIL treatment preceded treatment with BMS-247550 (20) [106]. It has also been reported that ectopic overexpression of Smac/DIABLO in human acute leukemia Jurkat T-cells or co-treatment with the N-terminal tetra-or heptapetide of this protein significantly enhance the apoptosis-inducing effects of BMS-247550 (20) in this cell line [107]. It is worth noting that Bhalla and coworkers strongly emphasize that their studies in A2780-1A9 cells would indicate that "apoptosis of A2780-1A9 cells follows [BMS-247550 (20)-induced] mitotic arrest, which is not associated with a marked increase in the levels of survivin" (cf., however, the recent work by Horwitz and coworkers [34,35]).…”
Section: Epothilone Analogs In Clinical Develop-mentsupporting
confidence: 52%
“…Similar differences have been observed for lactam-based analogs of Epo C and D, both of which are significantly less potent against P-gp-overexpressing human cancer cell lines than drug-sensitive lines [104]. Like other types of microtubule inhibitors BMS-247550 (20) was found by Bhalla and coworkers to induce G2/M arrest and apoptosis in human cancer cell lines [105]. As for Epo B [36] (vide supra), apoptosis induction in MDA-MB-468 human breast carcinoma cells appears to be related to a conformational change in the Bax protein and its subsequent translocation to the mitochondrial membrane [105].…”
Section: Epothilone Analogs In Clinical Develop-mentmentioning
confidence: 97%
See 3 more Smart Citations